IPMN and Parathyroid Adenoma: An Interesting Association - Gilshtein, Hayim; Mekel, Michal; Kluger, Yoram (JOP. Journal of the Pancreas, 2012)
No abstract available. Image: Plaque of Moses Maimonides (in Hebrew: Rav or Rabbi Moshe Ben Maimon, or "RaMBaM") at Rambam Medical Center. Haifa, Israel.